Melancholy Pride - Gelber, Mark H (Max Niemeyer Verlag, 2014)
This study focuses on the emergence of a modern Jewish national literature and culture within the parameters of Zionism in Vienna and Berlin at the turn of the last century. Prominent figures associated with early modern Zionism, including Theodor Herzl, Max Nordau, and Martin Buber, were also writers and literary or cultural icons within the Central European, Germanic-Austrian cultural environment of the fin-de-siècle. More important, Cultural Zionism promoted young Jewish literary and artistic talent as part of its ideology of a modern Jewish Renaissance. A corpus of German-language Jewish-national poetry and literature, as well as mechanisms for its dissemination and reception, developed rapidly. Most of this literary and cultural production has been forgotten or suppressed. Productive, if often unlikely, partnerships between Jewish national poets and artists and Central European cultural figures and movements were forged in this context. Facets of Central European cultural life, which were somewhat oppositional to traditional Jewish culture were received, absorbed, or transformed within Cultural Zionism. For example, the relationship of German racialist thought and German-nationalist fraternity life to early Jewish-national expression is a largely unknown chapter of early Jewish-national cultural history. The same can be said for the impact of feminist, counter-culture, and bohemian circles in Berlin on Cultural Zionist personalities and their work
10.1515/9783110956085
Keywords: German literature / Jewish authors / History and criticism; Jews / Germany / Intellectual life; Judaism and literature / Germany; Zionism / Germany / History; Deutsch; Deutschland; Judenbild; Literatur; Zionismus; HISTORY / General